Beyond the agroecological and sustainable agricultural intensification debate: Is blended sustainability the way forward?. Issue 2 (4th March 2018) - Mockshell, Jonathan; Kamanda, Josey
ABSTRACT: With the sustainable development goals has come a renewed global interest in ending hunger and achieving food security, while preventing natural resource degradation. Despite this renewed interest and increased commitments to invest in agricultural development, there is an outstanding debate over the technological trajectories to sustainability. The debate centres on sustainable agricultural intensification (SAI) and agroecological intensification (AEI) pathways to agricultural sustainability. Using a systematic literature review approach, this study examines the debate over AEI and SAI. This study employs a theoretical framework based on the economic, social, and ecological dimensions of sustainable agriculture within a policy and institutional space. Based on the sustainability dimensions, a discourse analytical technique is applied to unravel the debate. The results reveal differences in actor composition in the SAI and AEI pathways. Both pathways aim to promote food security with optimal and sustainable use of inputs; however, the actors differ on discourse relating to the concept of farming, the role of genetic engineering, the scale of operation, land use and soil health. Resolving these differences requires a blended sustainability approach that moves beyond the current AEI and SAI debate by acknowledging the tradeoffs and synergies of the socio-economic and ecological dimensions.